The Energy in the Room: Bodies Behaving Weirdly. (29th January 2013) - Cameron, Rose
ABSTRACT This paper elaborates Totton's claim that subtle energy throws into question our separateness as bodies. It examines embodied experience of "the energy in the room" and argues that, however such a quality of experience is theorised, understanding its dynamics is of importance to psychotherapists of different theoretical orientations. Copyright © 2013 John Wiley & Sons, Ltd.